Niccolò Machiavelli on Power - Holler, Manfred J.; Justus Liebig University Giessen (My University, 2009)
This paper uses the concept of power to analyze Machiavelli's The Prince and the Discourses on the First Ten Books of Titus Livius. This helps to distil the elements that form the Machiavelli program that has its short-term aim in the formation of a national state of Italy. A unification of Italy under the umbrella of a princely family (such as identified with Cesare Borgia) was meant to be the first stage in an evolutionary process which, in the end, could lead to a more or less stable republican system. For the latter, the Roman Republic as described in the Discourses is Machiavelli's model. The use of power, but also the minimization of cruelties, and the participation of the people, either in the form of militia to successfully fight foreign armies or to support the princely government, are major ingredients to this process.
Keywords: ddc:100; ddc:330